سلطة الضبط في القوانين الإعلامية الجزائرية (دراسة قانونية إعلامية - حمزة زياني; حليمة زيام; اشراف:محمدي اسمهان (جامعة محمد بوضياف. المسيلة, 2025)
ملخص: سلطات الضبط في قوانين الاعلام تشير إلى الجهات المسؤولة عن تنظيم ورقابة وإشراف على قطاع الإعلام ووسائل الإعلام المختلفة. تختلف هذه السلطات من دولة لأخرى وفقًا للتشريعات والسياسات الإعلامية المعمول بها. تتضمن سلطات الضبط في القانونين الإعلامي عادةً: الهيئات التنظيمية: تشمل الهيئات الحكومية أو الهيئات المستقلة التي تتولى تنظيم وإشراف على قطاع الإعلام وتحديد القواعد والمعايير التي يجب على وسائل الإعلام الالتزام بها. الهيئات الرقابية: تشمل الهيئات التي تتولى مراقبة ورصد وتقييم أداء وسائل الإعلام والتأكد من الامتثال للقوانين والمعايير المحددة. الهيئات القضائية: تشمل المحاكم والهيئات القضائية التي تتولى حل النزاعات والشكاوى المتعلقة بالإعلام وتطبيق العقوبات على المخالفين للقوانين الإعلامية. تهدف سلطات الضبط في القانونين الإعلامي إلى ضمان حرية التعبير والإعلام والوصول إلى المعلومات، وفي نفس الوقت تحمي المجتمع من الإساءة والتشويه والتحريض والتضليل من قبل وسائل الإعلام. تعتبر هذه السلطات أداة حيوية لتحقيق التوازن بين حرية الإعلام والمسؤولية الاجتماعية لوسائل الإعلام. الكلمات المفتاحية: الضبط، الاعلام، سلطة الضبط Abstract Regulatory authorities in media laws refer to the bodies responsible for regulating, monitoring, and supervising the media sector and various media outlets. These authorities differ from one country to another according to the applicable media laws and policies. Regulatory authorities in media laws typically include: Regulatory bodies: These include governmental or independent bodies that regulate and oversee the media sector and set the rules and standards that media outlets must comply with. Monitoring bodies: These include bodies that monitor, observe, and evaluate the performance of media outlets and ensure compliance with established laws and standards. Judicial bodies: These include courts and judicial bodies that resolve disputes and complaints related to the media and enforce penalties on violators of media laws. The aim of regulatory authorities in media laws is to ensure freedom of expression and media, as well as access to information, while at the same time protecting society from abuse, distortion, incitement, and misinformation by the media. These authorities are considered a vital tool for achieving a balance between media freedom and the social responsibility of media outlets. Keywords: Regulation, Media, Regulatory Authority.